From Co-operation in Central and Eastern Europe to European Union Partnership (Ympäristöministeriö, 2006)
Finland’s co-operation in the Baltic Sea region began during the major political realignment of the early 1990s. Environmental protection rapidly became a central theme of the co-operation programme. Finland began its co-operation in Central and Eastern Europe in 1990 by studying sites in northwest Russia and Estonia where urgent action was needed to improve the state of the environment. Co-operation also began later with Latvia and Lithuania. A co-operation programme known as ecoconversion began with Poland in 1991. As a result of co-operation in Central and Eastern Europe, international financing promoted water protection and other environmental projects seeking to reduce pollution in Russia, Estonia, Latvia, Lithuania and Poland. Over the last 15 years Finland has invested a total of EUR 106.5 million in grant aid for environmental protection projects in these countries and provided technical assistance to the value of EUR 44.1 million. The European Union has now enlarged to encompass most of northern Europe, effectively transforming the Baltic Sea into an inland sea of the Community. At the same time more than a decade of close bilateral project co-operation with the Baltic States and Poland came to an end when these countries became members of the European Union. Work to protect the Baltic Sea is nevertheless continuing. Such matters as increased oil transportation and discharges of harmful substances and agricultural effluent to the Baltic Sea will continue to require systematic measures and international co-operation. The role of co-operation in Central and Eastern Europe is changing in the direction of equitable partnership. For example, the Northern Dimension Environmental Partnership Support Fund (NDEP) brings together a wide range of financiers to assist local authority environmental protection investments in northwest Russia. One major challenge for Finland is to limit greenhouse gas emissions to the level imposed by the Kyoto Protocol to the United Nations Framework government has decided that ...